The Moderating Effect of Human Capital in the Investment-Growth Nexus: Evidence from MSME and Fixed Capital Formation in Indonesia - Yusnidar; Srinita; Muhammad Abrar (Arthatama: Journal of Business Management and Accounting, 2025)
This study examines the short-run effects of Micro, Small, and Medium Enterprise (MSME) investment and Gross Fixed Capital Formation (Pembentukan Modal Tetap Bruto/PMTB) on inclusive economic growth in Indonesia, with human capital incorporated as a moderating variable. Using annual time-series data from 1990 to 2024 sourced from the World Bank, the analysis applies Moderated Regression Analysis (MRA) with model refinement through heteroskedasticity-robust standard errors and mean-centering to address multicollinearity. The empirical results demonstrate that MSME investment and human capital exert strong and significant positive impacts on inclusive growth, whereas PMTB shows a positive but relatively weak direct effect. Importantly, human capital significantly amplifies the influence of both MSME investment and PMTB on inclusive economic growth, confirming its catalytic role in enhancing the productivity and inclusiveness of investment. This study contributes new empirical evidence on the moderating function of human capital within Indonesia’s investment–growth nexus by employing a rigorously corrected MRA framework on long-span time-series data, a methodological approach still limited in the existing literature.